Conceptual Bases of the İmpact of Ethnic Conflicts on Regional and İnternational Security - Najafov Zafar Nuri (Polit Journal Scientific Journal of Politics, 2021)
The article examines the impact of ethnic conflicts on regional and international security. It is noted that during the Cold War, it was impossible to conduct serious research in this area. Because ethnic conflicts were seen as an internal affair of states. However, with the end of the Cold War, the collapse of absolute sovereignty intensified the interaction between the domestic life of the country and the international community. Such a development in the context of globalization has turned ethnic conflicts into a problem of international politics, taking them out of the context of the internal affairs of states. The globalization of ethnic conflicts has strengthened its impact on regional and international security and laid the groundwork for the "ethnicization of international relations". The impact of ethnic conflicts on regional and international security can be studied in the context of instrumentalism, neomondialism, the Brubaker’s Triangle, ethno-political movements, and theories of protracted conflict. In the theory of instrumentalism, ethnic conflict is seen as a means of struggle by elites. Even this struggle serves the interests of the ruling forces not only within the country, but also abroad. In the theory of protracted social conflicts, the main processes revolve around internal conflicts and identities. The Brubaker’s Triangle and theories of the ethnopolitical movement play an important role in the study of the external resources of separatism and its transformation into an interstate war. In the context of neomondialism, S. Huntington's theory of "clash of civilizations" tried to justify the fact that future conflicts will occur between religious and civilizational systems stemming from cultural factors.